Biomechanics of the human eye sclera - Fazio,Massimo Antonio; Bruno,Luigi; Rizzuti,Sergio (My University, 2010)
The biomechanics of the optic nerve head and peripapillary sclera have been hypothesized to play a central role in the individual susceptibility to glaucoma, which is the second leading cause of blindness worldwide. The aim of this work is to provide a mechanical testing and experimental data analysis procedure to characterize mechanical properties of human sclera. The overall goal of performing scleral tissue mechanical testing is to elucidate the role of ocular biomechanics in the development of this disease by constructing eye-specific finite element models of the posterior pole. In this work it has been developed and validated a new methodology for computing sub-micrometer scale IOP-induced deformation obtained during pressurization testing of human scleral shells. Genetic Algorithm-based procedure and a microstructure-based numerical fitting method have been adopted to assess structural material properties of the testes eyes. Preliminaries results show the range of nonlinear, anisotropic mechanical properties of posterior sclera from normal eyes of human donors.
Dottorato di Ricerca in Ingegneria Meccanica, XXIII Ciclo,a.a. 2007-2010
Keywords: Biomeccanica; Occhio; Pressione intraoculare; Glaucoma; Processi